Malaysian Pharmacy Students’ Assessment of an Objective Structured Clinical Examination (OSCE) - Awaisu, Ahmed; Abd Rahman, Norny Syafinaz; Nik Mohamed, Mohamad Haniki; Rahman Bux, Siti Halimah Bux; Mohamed Nazar, Nor Ilyani (American Association of Colleges of Pharmacy (AACP), 2010)
Objective. To implement and determine the effectiveness of an objective structured clinical examination (OSCE) to assess fourth-year pharmacy students’ skills in a clinical pharmacy course. Design. A 13-station OSCE was designed and implemented in the 2007-2008 academic year as part of the assessment methods for a clinical pharmacy course. The broad competencies tested in the OSCE included: patient counseling and communication, clinical pharmacokinetics (CPK), identification and resolution of drug-related problems (DRPs), and literature evaluation/drug information provision. Assessment. Immediately after all students completed the OSCE, a questionnaire containing items on the clarity of written instructions, difficulty of the tasks, perceived degree of learning gained and needed, and the suitability of the references or literature resources provided was administered. More than 70% of the students felt that a higher degree of learning was needed to accomplish the tasks at the 2 DRP stations and 2 CPK stations and the majority felt the written instructions provided at the phenytoin CPK station were difficult to understand. Although about 60% of the students rated OSCE as a difficult form of assessment, 75% said it should be used more and 81% perceived they learned a lot from it. Conclusion. Althoughmost students felt that the OSCE accurately assessed their skills, amajority felt the tasks required in some stations required a higher degree of learning than they had achieved. This may indicate deficiencies in the students’ learning abilities, the course curriculum, or the OSCE station design. Future efforts should include providing clearer instructions at OSCE stations and balancing the complexity of the competencies assessed.